Dificultad respiratoria por deficiencia de surfactante pulmonar en neonato a término. - Arce Ibarra, Keyla Tatiana (2020)
Respiratory distress is defined as a syndrome where a clinical picture with difficulty breathing occurs due to the deficiency of pulmonary surfactant in this type of term neonate patient, because their lungs are not fully developed, therefore lead to this type of respiratory failure, the incomplete development of the lungs in the term neonate can be caused by different factors, they can be chemical, in addition to a morphological alteration and the functions of the organism, different alterations in the lungs appear that they do not have pulmonary surfactant, it is difficult for them to maintain proper ventilation and perfusion, correct hematosis, so the patient may present with generalized peripheral cyanosis that causes the hypoxemia that occurs in the patient. The present clinical case of a 33-week gestation neonate at term who was admitted to the neonatal intensive care area after 2 hours of birth presented difficulty breathing with oxygen desaturation, in addition to presenting distal cyanosis, arterial hypotension, for which This area was entered in order to be more careful and to establish non-invasive mechanical ventilation as a treatment method. Different tests were used in the diagnosis, such as X-rays, blood counts and blood gases, among others. In addition, the Silverman-Anderson rating scale was applied to determine the severity of the case.